2020
DOI: 10.1093/nargab/lqaa018
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and evolution of bacterial bioluminescence genes in the global ocean

Abstract: Although bioluminescent bacteria are the most abundant and widely distributed of all light-emitting organisms, the biological role and evolutionary history of bacterial luminescence are still shrouded in mystery. Bioluminescence has so far been observed in the genomes of three families of Gammaproteobacteria in the form of canonical lux operons that adopt the CDAB(F)E(G) gene order. LuxA and luxB encode the two subunits of bacterial luciferase responsible for light-emission. Our deep exploration of public mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 96 publications
1
15
0
Order By: Relevance
“…In fact, this has been proved to be able to activate the reduced flavin substrate resulting in a remarkable enhanced emission at 534 nm [238]. More generally, it is to remind how the evolution of luciferase enzymes is studied to better clarify the biodiversity distribution and functions of genes encoding for subunits participating to flavin based light emission, such as the luxA and luxB genes, leading to valuable outcomes in bacterial taxonomic studies [239].…”
Section: Bioluminescencementioning
confidence: 99%
“…In fact, this has been proved to be able to activate the reduced flavin substrate resulting in a remarkable enhanced emission at 534 nm [238]. More generally, it is to remind how the evolution of luciferase enzymes is studied to better clarify the biodiversity distribution and functions of genes encoding for subunits participating to flavin based light emission, such as the luxA and luxB genes, leading to valuable outcomes in bacterial taxonomic studies [239].…”
Section: Bioluminescencementioning
confidence: 99%
“…The enzymatic system responsible for light emission in luminous bacteria is one of the longest studied and one of the most complex [18,19]. Many aspects of its functioning under in vivo conditions and its biological role are still under consideration [16,20,21]. Bacterial luciferase, a key enzyme in the bioluminescent system, is a flavin-dependent monooxygenase utilizing reduced flavin mononucleotide, long-chain aldehyde, and oxygen as substrates [22].…”
Section: Introductionmentioning
confidence: 99%
“…Biosynthetic pathway of bacterial bioluminescence is one of the most thoroughly investigated among all luminescent organisms. To date, 25 characterized luminous bacterial species belong in three families of the Gammaproteobacteria: Shewanellaceae (Shewanella), Enterobacteriaceae (Photorhabdus), and Vibrionaceae (Aliivibrio, Photobacterium, and Vibrio) (Vannier et al, 2020). All luminescent bacteria utilize a singular mechanism for light emission and employ similar luciferases (Marquette and Blum, 2010).…”
Section: Bacterial Bioluminescent Systemmentioning
confidence: 99%
“…Despite their wide distribution in marine environments, ranging from free-swimming to symbiotic species, bioluminescent bacteria all carry a highly conserved luxCDAB(F)E(G) core (Dunlap and Urbanczyk, 2013), with minor variations correlated with environmental parameters (Brodl et al, 2018) and species life-style, such as symbiotic associations with squid or fish (Davis et al, 2016;Schwartzman and Ruby, 2016), observed in the lux operon architecture. A recent study employing metagenomic data analysis revealed a much wider diversity of lux operon sequences organization with novel lux genes and operons being more abundant in the global ocean than the canonical CDAB(F)E(G) operon (Vannier et al, 2020). Using structural information from the newly discovered individual enzymes of the overarching lux family and addressing evolutionary conserved areas within these structures will eventually provide insight on the evolutionary function and origin of bioluminescence.…”
Section: Bacterial Bioluminescent Systemmentioning
confidence: 99%